1998
DOI: 10.1016/s0002-9440(10)65614-3
|View full text |Cite
|
Sign up to set email alerts
|

Adenomatous Polyposis Coli Gene Mutation Alters Proliferation through its β-Catenin-Regulatory Function in Aggressive Fibromatosis (Desmoid Tumor)

Abstract: Aggressive fibromatosis is a monoclonal proliferation of spindle (fibroblast-like) cells. A subset of lesions contain somatic truncating adenomatous polyposis coli (APC) gene mutations, and all of the lesions contain an elevated beta-catenin protein level. A major function of APC is to regulate beta-catenin protein level. Beta-catenin has a dual function in the cell: it is a member of the adherens junction, and it binds transcription factors in the tcf-lef family, transactivating transcription. Cell cultures f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
83
0
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(87 citation statements)
references
References 18 publications
3
83
0
1
Order By: Relevance
“…The ␤-catenin and APC genes are closely interrelated and play a significant role in epithelial neoplasms, best studied in colon cancer (18, 26 -39), but also in deep fibromatoses (19,40) and sarcomas (41). ␤-catenin is an intracellular protein that is regulated by the APC protein.…”
Section: Discussionmentioning
confidence: 99%
“…The ␤-catenin and APC genes are closely interrelated and play a significant role in epithelial neoplasms, best studied in colon cancer (18, 26 -39), but also in deep fibromatoses (19,40) and sarcomas (41). ␤-catenin is an intracellular protein that is regulated by the APC protein.…”
Section: Discussionmentioning
confidence: 99%
“…The role of ␤-catenin as an oncoprotein has been analyzed so far in a number of epithelial tumors, an increased expression was also shown in aggressive fibromatosis as a representative of mesenchymal tumors (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…Expression and mutation of ␤-catenin and APC were described in aggressive fibromatosis, a subtype of mesenchymal tumors (21,22). APC mutations in the fibromatoses of FAP syndromes and the loss of chromosome 5q, the chromosomal localization of the APC gene in sporadic desmoid fibromatoses, indicate their relevance for the pathogenesis of fibromatoses as soft tissue tumors (22,23).…”
mentioning
confidence: 99%
“…They can occur as sporadic lesions or as part of familial adenomatous polyposis, which is caused by germline mutations in the adenomatous polyposis coli (APC) gene. Sporadic desmoids harbour somatic mutations in either the APC gene or in the b-catenin gene, resulting in b-catenin protein stabilisation (Li et al, 1988;Tejpar et al, 1999). Previously, we demonstrated constitutive TCF activation in primary desmoid cell cultures and showed that b-catenin binds and activates TCF-3 in these tumours (Tejpar et al, 2001).…”
mentioning
confidence: 93%